Mixed convection boundary layer flow past a horizontal circular cylinder embedded in a porous medium saturated by a nanofluid: Brinkman model - Tham, L.; Nazar, R.; Pop, I. (Begell House, 2013)
In this paper, the steady mixed convection boundary layer flow past a horizontal circular cylinder with a constant surface temperature and embedded in a porous medium saturated by a nanofluid in a stream flowing vertically upward has been studied by the Brinkman model for both cases of a heated and cooled cylinder. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme. Numerical results are obtained and discussed for the skin friction coefficient, the local Nusselt number, and the local Sherwood number, as well as the velocity, temperature, and nanoparticle volume fraction profiles, for various values of the governing parameters, namely, the mixed convection parameter, Darcy-Brinkman parameter, Lewis number, Brownian number, buoyancy ratio parameter, and thermophoresis parameter. From this study, it is found that the nanoparticle volume fraction improved the fluid-flow and heat-transfer characteristic